Parasitoid - Adam, Nur Azura; Md Yusof, Nur Athikah; Roseli, Marina (Universiti Putra Malaysia Press, 2013)
Parasitoid is a term used for insects that play the role of common parasite. They spend a significant portion of their life cycle in or on other organisms whereas the adult parasitoids are free-living creatures. Unlike their closely-related sister group, the wasp, their needle-like appendage, called ovipositor. Is used to lay eggs on or in their victims. The length of the ovipositor ranges from a millimeter up to 10 centimeters. Some species have a longer ovipositor which is 8 times their body length! The length varies deoending on the hots.